2010
DOI: 10.1186/1754-9493-4-6
|View full text |Cite
|
Sign up to set email alerts
|

The SURgical PAtient Safety System (SURPASS) checklist optimizes timing of antibiotic prophylaxis

Abstract: BackgroundSurgical site infection (SSI) is an adverse event in which a close relation between process of care and outcome has been demonstrated: administration of antibiotic prophylaxis decreases the risk of SSI. In our tertiary referral centre, a SURgical PAtient Safety System (SURPASS) checklist was developed and implemented. This multidisciplinary checklist covers the entire surgical pathway and includes, among other items, administration of antibiotic prophylaxis before induction of anaesthesia. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…The use of checklists in health care, however, has been much slower to evolve despite evidence that their use improves patient outcomes and/or improves team behaviours and communication. 5,[18][19][20][21][22][23] Specifically, use of the WHO SSC has shown a decrease in inpatient morbidity and mortality 2,[4][5][6][7]24 as well as improvement in teamwork skills, communication, and adherence to process measures. 1,23,[25][26][27] Nevertheless, Ko et al's recent systematic review of checklist use in medicine has shown limited evidence of their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The use of checklists in health care, however, has been much slower to evolve despite evidence that their use improves patient outcomes and/or improves team behaviours and communication. 5,[18][19][20][21][22][23] Specifically, use of the WHO SSC has shown a decrease in inpatient morbidity and mortality 2,[4][5][6][7]24 as well as improvement in teamwork skills, communication, and adherence to process measures. 1,23,[25][26][27] Nevertheless, Ko et al's recent systematic review of checklist use in medicine has shown limited evidence of their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As in the fi eld of aviation industry, in surgical practice also, to improve surgical quality and safety, checklists are introduced 2 . WHO has proposed the checklist for surgical procedure to improve team work and to build confi dence by decreasing avoidable errors.…”
Section: Discussionmentioning
confidence: 99%
“…Various checklists such as Surgical Patient Safety System (SURPASS) study showed in hospital morality reduced from 1.5% to 0.8% around the world. However it contains 124 items to be fi lled and its compliance with practitioners was not well assessed 2 . Nepal being a developing country lacks the system of digital medical records, well equipped operation theatre and well trained operation theatre staffs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not assume an impact on the timing or its documentation, as previously described in a retrospective cohort study. 21 Second, the SSI rate was studied in only a subset of patients. The subset of patients with cholecystectomy and colon resection was chosen as a sample for quality control in clean and clean-contaminated wounds.…”
Section: Discussionmentioning
confidence: 99%